Determination of Biodegradation Zone in Central Sumatra Basin - Jonathan Setyoko Hadimuljono; Nurus Firdaus (Testing Center for Oil and Gas LEMIGAS, 2021)
It is commonly known that heavy oil is mostly formed through biodegradation process within reservoir or on the surface both by aerobic and/or anaerobic bacteria that can live under specfi c temperature level(s). In order to investigate heavy oil occurences in Central Sumatra Basin, eff orts have been spent to determine the depths that represent the maximum temperature. By integrating the maximum viable temperature of typical bacteria and temperature gradient data, the depth of heavy oil zone is determined. The work is a combination of establishment of geothermal gradient map and laboratory analysis on fi eld sampled oil for determining types and temperature characteristics of microorganism living in the samples. Heavy oil sampling is made on seepages in areas nearby Minas fi eld. Subsequent laboratory analysis reveals Burkholderia multivorans ATCC BAA-247 as the predominant bacteria having maximum viabl temperature of 60Â° C. Based on the established geothermal gradient map, this maximum temperature correspond to average depth of 1818 ft (555.5 m). This average depth is used as the lower depth for the biodegradation zone over which investigation over presence of heavy oil bearing reservoirs/traps is made.